CHANGES IN BIOACTIVE COMPOUNDS STABILITY AND COLOUR OF FUNCTIONAL PLUM SPREAD DURING DIFFERENT STORAGE CONDITIONS - Bajić, Aleksandra; Mastilović, Jasna S.; Cvetković, Biljana R.; Ubiparip Samek, Dragana N.; Djordjević, Marijana Z.; Djordjević, Miljana Z.; Dragojlović, Danka M. (Food and Feed Research, 2024)
There is growing interest in utilizing juice pomace, including plum pomace, in new food products as a sustainable strategy for reducing waste and providing an alternative source of dietary fibers and phenolic bioactives in the functional food. Some phenolics, such as anthocyanins are more sensitive and susceptible to degradation processes in fruit preparation during storage. This study aimed to assess the effect of a storage period and temperature on the retention of phenolics, anthocyanins (total and monomeric) and colour of functional plum spread enriched with plum pomace. The spreads were stored at 4 °C (14 days) and at 20 or 40 °C for 14, 28 and 45 days. Control sample, was also subjected to analysis one day after production and obtained measurements for investigated spreads were compared. Results revealed that total phenolics remained more stable than total anthocyanins and total monomeric anthocyanins at room temperature, while a temperature of 40 °C led to the loss of all bioactives. Colour deterioration was observed in all samples, with the least change at 4 °C. Refrigeration of sperad was found to significantly slow down the loss of phenolics and anthocyanins and better preserve colour.